TINGKAT KEMAMPUAN BERPIKIR KREATIF MATEMATIKA SISWA SMP KELAS VIII DI SMP NEGERI 6 JEMBER, SMP AL FURQAN 1, SMP NEGERI 1 RAMBIPUJI, DAN SMP PGRI 1 RAMBIPUJI - Arifani, Nurul Hidayati; Sunardi, S; Setiawani, Susi (KadikmA, 2015)
Abstract. The research aims to measure the level of creative thinking ability of math for Junior High School students in 8th year class especially in SMP Negeri 6 Jember, SMP Al Furqan 1, SMP Negeri 1 Rambipuji, and SMP PGRI 1 Rambipuji. The research methods are test with open ended problems and interview. The research shows that 2,84% students are in very high level of creative thinking, 2,84% are in high level of creative thinking, 21,49% are in the middle level of creative thinking, 29,75% are in low level of creative thinking, and 43,80% are in very low level of creative thinking among total 121 students. This shows that the creatitive thinking of math for students in 8th year class especially in SMP Negeri 6 Jember, SMP Al Furqan 1, SMP Negeri 1 Rambipuji, and SMP PGRI 1 Rambipuji are still low. Key Words: creative thinking, open ended problems